Perbedaan Jenis Bahan Terhadap Hasil Teknik Double Controlled Pleats pada Mini skirt - Nurfadhila, Emi; Nelmira, Weni (Universitas Batanghari Jambi, 2025)
Double Controlled Pleats is a type of pleat on clothing that is loose in the middle so that it produces a three-dimensional effect. The application of double controlled pleats on clothing is still rarely found. This study aims to analyze the differences in material types on the results of the double controlled pleat fabric technique on mini skirts in terms of the stability of the pleat shape, neatness of the pleats, proportions, and aesthetic value using bridal and shantung satin materials. This study is an experimental study with a quantitative method. The type of primary data with an assessment carried out by 18 panelists, the assessment results were processed using quantitative descriptive analysis and inferential analysis with the help of SPSS 25. The results showed that there were significant differences in the finished results of double controlled pleat fabric on bridal and shantung materials in terms of the stability of the pleat shape and neatness of the pleats while in terms of proportion and aesthetic value there were no significant differences. The Independent T-Test for differences in material types on the finished results of double controlled pleats obtained t-count <significance = 0.000 <0.05. Thus it can be concluded that there are differences in the types of materials on the finished results of double controlled pleats.